Учет механических напряжений в комбинированных диэлектриках для конденсаторов СБИС - Пилипенко, В.А.; Пономарь, В.Н.; Петлицкая, Т.В. (Технология и конструирование в электронной аппаратуре, 2003)
Предложен вариант комбинированного конденсаторного диэлектрика на основе пентаоксида тантала для конденсаторов СБИС. Для поиска оптимального сочетания слоев, при котором система Si — SiO₂ — Ta₂O₅ не испытывает упругой механической деформации, была построена модель упругих напряжений. Расчет показал, что при соотношении толщины пленок Ta₂O₅ и SiO₂ как 1:10 радиус кривизны пластины со сформированными диэлектриками стремится к бесконечности, а сама кривизна – к нулю. Рассчитаны упругие постоянные для пленки Ta₂O₅. Owing to rise in VLSIC integration, searching for new materials for VLSIC capacitor becomes significant. There was proposed a version of combined capacitor dielectric for VLSIC capacitors on basis of tantalum pentaoxide. Pentaoxide of tantalum has a very high permittivity and good technological compatibility with silicon oxide. The peculiarity of two-layer combined dielectric SiO₂—Ta₂O₅ is that the polarity of voltages development in the systems Si—SiO₂ and Si—Ta₂O₅ has different values. To find an optimal combination of layers when the system does not experience mechanical elastic deformation, there was built a model of elastic stresses in the system Si—SiO₂—Ta₂O₅. The calculations showed, when width of Ta₂O₅ and SiO₂ are in the ratio 1:10, wafer radius of curvature with formed dielectrics approaches infinity, the curvature itself – zero. Besides that, based on experimental data and by means of mathematical mode, there were calculated elastic constants for Ta₂O₅ film.